DAMPAK PEMBELAJARAN DARING MASA PANDEMI COVID 19 (STUDI KASUS PADA ORANG TUA PESERTA DIDIK) - Andi Yurni Ulfa (Jurnal Pendidikan Sang Surya, 2021)
This study aims to know(i) Positif impact on learning of online pandemic COVID 19  for student parent who are working as farmers. (ii) Negatif  impact on learning of online pandemic COVID 19  for student parent who are working as farmers. The research was classified as qualitative research with an case study methode. The instrument used on this study researcher becomes the key instrument. The data were collected using participants observations, interview and document studies. The data were analyzed using the Miles & Huberman model.Based on the result of data analysis in the concluded: (i) Positif impact on learning of online pandemic COVID 19  for student parent who are working as farmers is their children are able to learn online using mobile phones with various applications. (ii) Negative impact on learning of online pandemic COVID 19  for student parent who are working as farmers is the network issues, quotas, their children are as severely as pain as it is less than taking a lot of work from the teachers, their child rarely helps the parents at the house and in the garden because of learning time that is very solid.